The impact of escitalopram on vagally mediated cardiovascular function to stress and the moderating effects of vigorous physical activity: a randomized controlled treatment study in healthy participants - Hanson, Camilla S.; Outhred, Tim; Brunoni, Andre R.; Malhi, Gin S.; Kemp, Andrew H. (Frontiers in Physiology, 2013)
Recent concerns over the impact of antidepressant medications, including the selective serotonin reuptake inhibitors (SSRIs), on cardiovascular function highlight the importance of research on the moderating effects of specific lifestyle factors such as physical activity. Studies in affective neuroscience have demonstrated robust acute effects of SSRIs, yet the impact of SSRIs on cardiovascular stress responses and the moderating effects of physical activity remain to be determined. This was the goal of the present study, which involved a double-blind, randomised, placebo-controlled, cross-over trial of a single-dose of escitalopram (20mg) in 44 healthy females; outcomes were heart rate and its variability. Participants engaging in at least 30 minutes of vigorous physical activity at least 3 times per week (regular exercisers) showed a more resilient cardiovascular stress response than irregular vigorous exercisers, a finding associated with a moderate effect size (Cohen’s d=0.48). Escitalopram attenuated the cardiovascular stress response in irregular exercisers only (heart rate decreased: Cohen’s d=0.80; heart rate variability increased: Cohen’s d=0.33). Heart rate during stress under escitalopram in the irregular exercisers was similar to that during stress under placebo in regular exercisers.. These findings highlight that the effects of regular vigorous exercise during stress are comparable to the effects of an acute dose of escitalopram, highlighting the beneficial effects of this particular antidepressant in irregular exercisers. Given that antidepressant drugs alone do not seem to protect patients from cardiovascular disease, longitudinal studies are needed to evaluate the impact of exercise on cardiovascular stress responses in patients receiving long-term antidepressant treatment.